Kajian Dan Simulasi Prinsip Kerja Coded Orthogonal Frequency Division Multiplexing Untuk Sistem Transmisi Radio Over Fibe - Raissa Lynn; Yohanes Calvinus (TESLA: Jurnal Teknik Elektro, 2018)
The fiber optics communication system is so far known to offer the highest information bandwidth, and has been intensively deployed world wide. This superior technological merit is fundamentally related to its use of high frequency optical carrier. However, optical fiber communication system requires the installation of fiber optics cable for the optical data transmission. This implied its restricted applications to user at fixed positions. On the other hand, the open air cellular communication technology has offered the high mobility and flexibility for the users. The obvious benefit of combining the two systems has led to the development of new technology that integrates optical fiber communication system with wireless communication system to provide great communication mobility with wide bandwidth. The integrated system (hybrid system) is known as the Radio over Fiber (RoF) system . In RoF system , traffic congestion problems between mobile phones via the Base Station (BS) and Remote Antenna Unit (RAU) can be reduced. In this final project, RoF communication system within the LAN network is considered. The realization of this model employs the Orthogonal Frequency Division Multiplexing (OFDM) method, which is equipped with convolution code technique, multi- mode optical fiber, Quadrature Amplitude Modulation (QAM) technique for digital modulation technique. In addition to that, the model also adopt Intensity Modulation-Direct Detection (IM–DD) technique for electro optic - opto electric conversion process. The system performance is analyzed and evaluated on the bases of Bit Error Rate (BER) variation versus the optical fiber’s transmission length for a selection of LD’s and PIN photodetectors as well as different multimode optical fibers. Untuk memenuhi kebutuhan informasi pita lebar yang semakin tinggi, teknologi serat optik adalah solusi yang paling tepat. Keunggulan ini berkaitan dengan teknologi serat optik yang mempunyai gelombang pembawa berupa gelombang optik dengan frekuensi gelombang sangat tinggi dan lebar pita transmisi yang sangat besar. Namun, pada sisi lain operasi sistem komunikasi serat optik memerlukan tersedianya kabel serat optik dalam proses pengiriman informasi. Hal ini mengakibatkan mobilitas para pengguna menjadi terhambat. Keadaan ini mendorong perkembangan teknologi baru yang mengintegrasikan sistem komunikasi serat optik dengan sistem komunikasi nirkabel untuk memberikan mobilitas komunikasi yang besar. Sistem gabungan (sistem hibrida) ini adalah sistem Radio over Fiber (RoF). Dalam sistem RoF, lalu lintas (traffic) yang sangat padat antara handphone melalui Base Station (BS) dan Remote Antenna Unit (RAU) dapat disalurkan dengan hubungan serat optik. Dalam tugas akhir ini teknik Orthogonal Frquency Division Multiplexing (OFDM) yang dilengkapi dengan teknik pengkodeean kanal kode konvolusi, serat optik multi mode, teknik modulasi Quadrature Amplitude Modulation (QAM) dan teknik Intensity Modulation – Direct Detection (IM-DD) untuk proses konversi elektro optik – opto elektrik. Kinerja sistem ini diuji dan dianalisa berdasarkan karakteristik variasi Bit Error Rate (BER) terhadap jarak tempuh serat optik untuk sejumlah pilihan komponen/modul dalam sistem.